Pharmacokinetic interaction between liquiritigenin (LQ) and DDB: Increased glucuronidation of LQ in the liver possibly due to increased hepatic blood flow rate by DDB - Kang, Hee E.; Chung, Hye J.; Kim, Hyung S.; Lee, Jee W.; Lee, Myung G. (ELSEVIER SCIENCE BV, 2010)
It has been reported that both liquiritigenin (LQ) and dimethyl-4,4'-dimethoxy-5,6,5',6'-dimethylenedioxybiphenyl-2,2'-dicarboxylate (DDB) have a hepatoprotective effect, and administration of both drugs together shows additive protective effect against acute liver injuries. Therefore, the pharmacokinetic interaction between LQ and DDB in rats was studied. LQ (20 and 50 mg/kg for the i.v. and p.o. administration, respectively), DDB (10 mg/kg for both i.v. and p.o. administration), and both drugs together were once administered intravenously or orally to rats. After the . administration of both drugs together, the Cl-nr and AUC of LQ were significantly faster (by 30.5%) and smaller (by 22.5%). respectively, than those of without DDB clue to the faster hepatic blood flow rate by DDB. After the p.o. administration of both drugs together, the AUC of LQ was comparable to that of without DDB due to negligible effect of DDB on intestinal metabolism of LQ The pharmacokinetic parameters of DDB after both i.v. and p.o. administration were not altered by LQ indicating that LQ did not considerably affect the pharmacokinetics of DDB in rats. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: DIMETHYL-4,4' -DIMETHOXY-5,6,5' ,6' -DIMETHYLENE DIOXYBIPHENYL-2,2' -DICARBOXYLATE; GLYCYRRHIZAE-RADIX; HPLC METHOD; METABOLISM; MICROSOMES; CLEARANCE; AGLYCONE; PLASMA; INDUCE; LEVEL